The Cost of Empowerment: Multiple Sources of Women's Debt in Rural India. Issue 5 (4th May 2017) - Garikipati, Supriya; Agier, Isabelle; Guérin, Isabelle; Szafarz, Ariane
Abstract: Poor women borrow from multiple sources. This study examines whether the source of debt matters for women's role in household financial decisions. Drawing on a household survey from rural Tamil Nadu, we categorise women's loans along the lines of accessibility and formality into 'planned loans' and 'instant loans'. We find that 'instant loans' support women's bargaining power in various types of household financial decisions, whereas 'planned loans' have no impact. This surprising result is better understood when the nature of 'instant loans' is examined – these are frequently usurious, involve coercive enforcement methods and are considered socially debasing. Hence women who use them perform a convenient role for their households and in return gain some negotiating power.